Racial Issues and their Influences on the Characters in Shakespeare’s Othello - Arfian Giri Prabowo (Lexicon, 2012)
This study aims to describe the racial issues found in Othello and to analyze the influence of the issues on the characters in the play. In finding racial issues, the present writer analyses dialogues between the characters in the drama implicitly and explicitly.The author uses Abrams‘ objective approach and also some references to classify the racial issues and along with the characters based on the types of racism such as individual racism, passive racism, active racism, and internalized racism. The data were obtained by observing the play without being influenced by materials outside of the text.The result of this study indicates that there are racial issues in this play. The racial issues have a very significant effect on the characters‘ view, including Othello‘s, of the existence of black people. Othello becomes racist against himself and loses the confidence of being black, hence the cause of the fall of Othello.